Triple Positive Solutions of a Nonlocal Boundary Value Problem for Singular Differential Equations with p-Laplacian. (13th March 2013) - Wang, Jufang; Yu, Changlong; Guo, Yanping
Abstract : We establish the existence of triple positive solutions of an m -point boundary value problem for the nonlinear singular second-order differential equations of mixed type with a p -Laplacian operator by Leggett-William fixed point theorem. At last, we give an example to demonstrate the use of the main result of this paper. The conclusions in this paper essentially extend and improve the known results.